Proust and Eliot: An Intertextual Reading - Inge Crosman Wimmers (Studies in 20th & 21st Century Literature, 2012)
Defining intertextuality as “the reader’s perception of relationships between one work and others, which either preceded or followed it” (Riffaterre), this essay sets out to highlight compelling similarities between Proust’s novel, A la recherche du temps perdu, and the fictional works of George Eliot. The emphasis is on affective memory (involuntary memory and emotional templates), ethical considerations (empathy and compassion), and the kind of self-reflexive reading both writers encourage through a complicit narration that implicates the reader. They show readers how emotional memory constitutes the essence of their personal history, thus anticipating modern research in psychology and the neurosciences. In doing so, they make us aware that there are no insurmountable barriers between fictional worlds and ours. In conclusion, this intertextual reading of two novelists from different centuries and cultures has confirmed that these insights are still valid today.
Keywords: intertextuality; Proust; A la recherche du temps perdu; George Eliot; affective memory; memory; ethics; fiction; fictional worlds; reality